1997
DOI: 10.1007/bf03015372
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular perforation associated with central venous introducerdilator systems

Abstract: Purpose: Cardiac perforation is a recognised complication of guidewire-introducer techniques. These two new cases of right ventricular perforation implicate the dilator-introducer: one directly and the other due to presumed guidewire buckling.Clinical Features: An 85-yr-old man underwent fight subclavian cannulation for triple-lumen and pulmonary artery (PA) catheter insertion before coronary artery surgery. Tachycarclia (120 bpm) and hypotension (60130 mmHg) evolved over the next 40 rain and resolved with eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…Dilator shaft width has been reported to vary from 6 to 12 French [10], with lengths of 10–19 cm [10] and 6–21 cm [11]. For most procedures, the length of dilators provided in CVC kits has been reported as excessive [10–13]. Depth markings along the dilator's length are lacking.…”
Section: Dilator Width/lengthmentioning
confidence: 99%
See 3 more Smart Citations
“…Dilator shaft width has been reported to vary from 6 to 12 French [10], with lengths of 10–19 cm [10] and 6–21 cm [11]. For most procedures, the length of dilators provided in CVC kits has been reported as excessive [10–13]. Depth markings along the dilator's length are lacking.…”
Section: Dilator Width/lengthmentioning
confidence: 99%
“…A number of cases of dilator‐related and suspicious dilator‐related and/or dilator/sheath‐introducer‐related complications have been discussed in the literature [10–13,15–29]. Jobes et al [16] reported inadvertent intra‐arterial placement of a 20‐gauge catheter/sheath‐introducer intended for internal jugular placement, which upon removal required local pressure for an “insignificant hematoma.” The patient was initially stable but died 12 hours later of exsanguination and a right hemothorax.…”
Section: Literature Review and Clinical Casesmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, the complications are divided into early and late categories. Early complications include pneumothorax and chylothorax [2], injury of carotid or subclavian arteries or even aortic arch [3], arteriovenous fistula [4], ventricular perforation [5], pericardial tamponade [6], air embolization, blindness [7], stroke and arrhythmias. Late complications include infection, thrombosis, pericardial effusion, and late mediastinal hemorrhage due to erosion of the vessels [8].…”
Section: Introductionmentioning
confidence: 99%